2020
DOI: 10.1038/s41390-019-0728-6
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine mitigates acute opioid withdrawal behaviors and CNS oxidative stress in neonatal rats

Abstract: BACKGROUND: Neonatal abstinence syndrome (NAS) is a significant problem. Opioid withdrawal induces oxidative stress and disrupts glutamate and glutathione homeostasis. We hypothesized that N-acetylcysteine (NAC) administered during acute opioid withdrawal in neonatal rats would decrease withdrawal behaviors and normalize CNS glutathione and glutamate. METHODS: Osmotic minipumps with methadone (opioid dependent, OD) and saline (Sham) were implanted into Sprague Dawley dams 7 days prior to delivery. Pups were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Alterations of specific physiological functions are responsible for the individual signs of withdrawal observed 21 . The withdrawal signs investigated were diarrhea, weight loss, mean number of jumps per 60 minutes, and mean number of abdominal contractions 14,[22][23][24] . Research provides evidence suggesting an association of the cholinergic system with biological activity of opiates 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of specific physiological functions are responsible for the individual signs of withdrawal observed 21 . The withdrawal signs investigated were diarrhea, weight loss, mean number of jumps per 60 minutes, and mean number of abdominal contractions 14,[22][23][24] . Research provides evidence suggesting an association of the cholinergic system with biological activity of opiates 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Although in vivo testing in human neonates is limited by ethical constraints (i.e., positron emission tomography scanning with radiotracers for opioid receptors), we may test salivary cortisol as a non-invasive measure of stress and measure oxidative stress in the brain via non-invasive magnetic resonance spectroscopy (Moss et al, 2018 ). While both of these markers are associated with opioid withdrawal (Ward et al, 2020 ), they are not direct measures of endogenous opioid release by tAN vs. another mechanism. Therefore, precise elucidation of mechanism relies on laboratory models of NOWS or pain models of neuromodulation of these cranial nerves.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Opioids and N-acetylcysteine NAC has been shown to produce positive outcomes in rodents for opioids (29), and a recent study in opioiddependent neonatal rats demonstrated that NAC mitigated behavioral withdrawal symptoms and oxidative stress (67). However, the efficacy of NAC in opioid dependence has not yet been tested in clinical populations (24), neither as a stand-alone treatment nor in addition to opioid-replacement therapies or behavioral treatment (3).…”
Section: Nicotine and N-acetylcysteinementioning
confidence: 99%